HISTOMORPHOMETRIC AGE EVALUATION USING SECONDARY DENTIN IN ADULT TEETH WITH AND WITHOUT OCCLUSAL ATTRITION - Wafaa Yahia Alghonemy; Fatma Rashed (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This research aimed to assess the correlation between the age of both males and females and the surface area of secondary dentin (SD) in the transverse ground section of human teeth with and without occlusal attrition. Eighty extracted sound teeth were allocated into four groups: Group I, 20 teeth without occlusal attrition from male patients; Group II, 20 teeth without occlusal attrition from female patients; Group III, 20 teeth with occlusal attrition from males; Group IV, 20 teeth with occlusal attrition from females. Later, transverse sections at the cervical third of each tooth root were prepared and examined. The correlation between the surface area of SD and the actual age together with patients’ sex was determined utilizing Pearson’s correlation coefficient. Linear regression was also calculated to study the relationship between the SD surface areas as a predictor of patients' age. From the obtained data, the chronological age was statistically significant, with a surface area of SD among all groups. The females showed a strong correlation, and the males showed a non-significant correlation between the chronological age and SD surface area. As well as, both teeth with occlusal attrition and those without occlusal attrition demonstrated a strong correlation between surface area and chronological age. The current research has highlighted the viability of using SD for age estimation in Egyptian adults for both sexes; however, the teeth showed occlusal attrition. Also, using the regression equations developed from this study specific to the sex and the tooth condition, dental age can be estimated by measuring the SD surface area from the histologic ground section.